Integrative taxonomy of Malagasy treefrogs: combination of molecular genetics, bioacoustics and comparative morphology reveals twelve additional species of Boophis - Glaw, Frank; Köhler, Jörn; de La Riva, Ignacio; Vieites, David R.; Vences, Miguel (Zootaxa, 2010)
We describe ten new species of treefrogs assigned to the genus Boophis (Anura: Mantellidae) and resurrect two species from synonymy, based on materials collected during fieldwork in Madagascar, carried out mainly between 2000 and 2007. Our comparative database assembled over the past years comprises fresh material for molecular analysis from all 58 nominal Boophis species, and advertisement call recordings from all except three species. We follow an integrative approach and combine molecular, bioacoustic and morphological evidence to diagnose the new species. In most cases, the new species have uncorrected molecular divergences of over 4–5% in the mitochondrial 16S rRNA gene to their closest relatives. In some cases the divergences are lower (2–2.5%) but are then accompanied by distinct differences in advertisement calls or morphology. Boophis piperatus sp. nov. from Ranomafana National Park is a small brown species assigned to the B. majori group that is similar to B. miniatus but differs in morphology and advertisement calls. Boophis arcanus sp. nov. is assigned to the B. majori group as well and is known from only two female specimens from a site close to Ranomafana; it is described mainly based on its strong genetic differentiation (> 7.2% to all other species). Boophis entingae sp. nov. is a species of the Boophis goudoti group occurring in northern Madagascar, similar to and sympatric with B. brachychir, but with a strongly different advertisement call. Boophis roseipalmatus sp. nov. belongs to the B. goudoti group, is similar to B. madagascariensis, and appears to replace this species in most of northern Madagascar, with possible areas of sympatry in the north east. Boophis spinophis sp. nov. is an enigmatic, morphologically highly divergent species from Ranomafana National Park that belongs into the B. goudoti group but differs from all other spe-4 · Zootaxa 2383 © 2010 Magnolia Presscies in the group by having distinct dermal tubercles along the lateral parts of the shank and around the elbow. Boophis praedictus sp. nov. is a sibling species of B. albilabris in the B. albilabris group, diagnosable by its red iris periphery and distributed in rainforest along the east coast. Boophis sandrae sp. nov. belongs to the B. luteus group and is superficially similar to the sympatric B. elenae, but has a faster call and smaller body size. Boophis miadana sp. nov. and B. haingana sp. nov., both in the B. albipunctatus group and syntopically occurring at Andohahela National Park, are related to B. ankaratra and B. schuboeae and differ mainly by their advertisement calls. Boophis luciae sp. nov., also in the B. albipunctatus group, differs from the sympatric B. albipunctatus and B. sibilans by having slightly smaller body size and different advertisement calls. We furthermore resurrect Rhacophorus obscurus Boettger, 1913 (as Boophis obscurus in the B. goudoti group) from the synonymy of Boophis goudoti as well as Rhacophorus andrangoloaka Ahl, 1928 (as Boophis andrangoloaka in the B. microtympanum group) from the synonymy of Boophis rhodoscelis, and propose to consider Rhacophorus brevirostris Ahl, 1928 as junior synonym of Boophis andrangoloaka. We discuss our integrative methodological approach and the different lines of evidence used to delimitate the species described or resurrected herein. By applying IUCN Redlist criteria, we evaluate the threat status of the species considered: six species are classified Data Deficient (B. arcanus, B. haingana, B. miadana, B. piperatus, B. praedictus, B. spinophis), four Vulnerable (B. andrangoloaka, B. entingae, B. roseipalmatus, B. sandrae), and two Least Concern (B. luciae, B. obscurus).